Little women - Alcott, Louisa May (Boston, Mass : Thomson Heinle, 2005)
Chronicles the joys and sorrows of the four March sisters as they grow into young ladies in nineteenth-century New England
Title from container
Keywords: March family (Fictitious characters) -- Juvenile fiction; Families -- New England -- Juvenile fiction; Sisters -- New England -- Juvenile fiction